2006
DOI: 10.4049/jimmunol.177.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Tight Linkage between Translation and MHC Class I Peptide Ligand Generation Implies Specialized Antigen Processing for Defective Ribosomal Products

Abstract: There is mounting evidence that MHC class I peptide ligands are predominantly generated from defective ribosomal products and other classes of polypeptides degraded rapidly (t1/2 < 10 min) following their synthesis. The most direct evidence supporting this conclusion is the rapid inhibition of peptide ligand generation following cycloheximide-mediated inhibition of protein synthesis. In this study, we show that this linkage is due to depleting the pool of rapidly degraded proteins, and not to interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 33 publications
2
92
2
1
Order By: Relevance
“…Interestingly, proteasome inhibition increased the accumulation of fluorescent, properly conformed GFP-SL8 by nearly 40%, suggesting that a subset of newly synthesized proteasomedegraded GFP might not be irreversibly misfolded and can become fluorescent if provided with enough time to fold. 35 Conversely, autophagy inhibition only weakly increased fluorescent GFP-SL8 levels, while it enhanced antigen presentation by almost 40% (Fig. 5C).…”
Section: Do Not Distributementioning
confidence: 92%
“…Interestingly, proteasome inhibition increased the accumulation of fluorescent, properly conformed GFP-SL8 by nearly 40%, suggesting that a subset of newly synthesized proteasomedegraded GFP might not be irreversibly misfolded and can become fluorescent if provided with enough time to fold. 35 Conversely, autophagy inhibition only weakly increased fluorescent GFP-SL8 levels, while it enhanced antigen presentation by almost 40% (Fig. 5C).…”
Section: Do Not Distributementioning
confidence: 92%
“…The observation that peptides generated in the cytosol by different processes access the class I pathway differently helps explain the puzzling discrepancy between the ability of peptides from DRiPs versus "retirees" to access the class I pathway (29,30) and the ability of exogenous antigens to avoid competition from endogenous peptides in accessing the class I pathway. This is likely an example of a cellular process that enhances its efficiency through physical or physiochemical compartmentalization (23,31).…”
Section: Discussionmentioning
confidence: 99%
“…This was implied by the dependence of overall peptide generation on protein synthesis [47,119], despite the unabated degradation of the proteome during acute CHXinduced protein synthesis blockade [57,120] (see Fig. 1 in ref. [120]).…”
Section: Compartmentalized Translation Degradation and Antigen Procmentioning
confidence: 99%
“…1 in ref. [120]). Differential substrate access was observed when expressing rapidly versus relatively slowly degraded, full-length proteasome substrates (half-lives of 10 min vs. 70 min), the latter of which is presented at twice the efficiency per protein degraded [46], or with canavanine-misfolded proteins, where RDPs were preferentially presented over slowly degraded forms [120]. Furthermore, competition studies [121] revealed that DRiP-derived SIINFEKL is presented in a manner that completely avoids competition with high-affinity, K b -binding, 8-mer peptides, generated in excess amounts in the cytosol from direct synthesis of minigenes or by proteolytic liberation from ubiquitin-fusion proteins.…”
Section: Compartmentalized Translation Degradation and Antigen Procmentioning
confidence: 99%